THE EVOLUTION OF PLUME BENEATH CONTINENTAL LITHOSPHERE WITH DRASTIC VARIATIONS IN THICKNESS - Tychkov S.A.; Vasilevskii A.N.; Rychkova E.V. (My University, 1999)
Numerical modeling of the evolution of plume beneath continental lithosphere with drastic variations in thickness is performed. It is shown that plume beneath continental lithosphere behaved differently than that beneath oceanic lithosphere, where the plume upwelling resulted in basalt magmatism and formation of a swell extending in the direction of the plate movement. Plume beneath ancient Precambrian continental platform gave rise to a swell, disturbance of potential fields, and local anomalies of heat flow (the result of hot-fluid upwelling along deep faults). Similar events might have occurred in the northwest of the Siberian Platform, where in the Late Cenozoic a swell more than 1 km high and 500-700 km in diameter (Putorana Plateau) formed. In active intracontinental areas, interaction between plume and asthenospheric convective flows took place. These flows transported the plume to thinned (<100 km) lithosphere, where its decompressive melting occurred. A similar mechanism of plume evolution acted in the Baikal Rift Zone. It might be responsible for the fact that Late Cenozoic basalt fields occur more than 200 km southeast of the BRZ.
Keywords: Precambrian; Cenozoic; Кайнозой; Cenozoic; Precambrian; Докембрий